Vitamin D Deficiency Aggravates the Renal Features of Moderate Chronic Kidney Disease in 5/6 Nephrectomized Rats - de Bragança, Ana Carolina; Canale, Daniele; Gonçalves, Janaína Garcia; Shimizu, Maria Heloisa Massola; Seguro, Antonio Carlos; Volpini, Rildo Aparecido (Frontiers in Medicine, 2018)
The pathogenesis of chronic kidney disease (CKD) involves a very complex interaction between hemodynamic and inflammatory processes, leading to glomerular/vascular sclerosis, and fibrosis formation with subsequent evolution to end-stage of renal disease. Despite efforts to minimize the progression of CKD, its incidence and prevalence continue to increase. Besides cardiovascular diseases and infections, several studies demonstrate that vitamin D status could be considered as a non-traditional risk factor for the progression of CKD. Therefore, we investigated the effects of vitamin D deficiency (VDD) in the course of moderate CKD in 5/6 nephrectomized rats (Nx). Adult male Wistar rats underwent Sham surgery or Nx and were subdivided into the following four groups: Sham, receiving standard diet (Sham); Sham VDD, receiving vitamin D-free diet (VDD); Nx, receiving standard diet (Nx); and VDD+Nx, receiving vitamin D-free diet (VDD+Nx). Sham or Nx surgeries were performed 30 days after standard or vitamin D-free diets administration. After validation of vitamin D depletion, we considered only Nx and VDD+Nx groups for the following studies. Sixty days after surgeries, VDD+Nx rats exhibited hypertension, a greater decline in renal function and plasma FGF-23 levels, renal hypertrophy, as well as higher plasma levels of PTH and aldosterone. In addition, those animals presented more significant chronic tubulointerstitial changes (cortical interstitial expansion/inflammation/fibrosis), higher expression of collagen IV, fibronectin and α-smooth muscle actin, and lower expressions of JG12 and M2 macrophages. Also, VDD+Nx rats had greater infiltration of inflammatory cells (M1 macrophages and T-cells). Such changes were accompanied by higher expression of TGF-β1 and angiotensinogen and decreased expression of VDR and Klotho protein. Our observations indicate that vitamin D deficiency impairs the renal function and worsens the renovascular and morphological changes, aggravating the features of moderate CKD in 5/6 nephrectomized rats.